Creating a Eurasian Union : economic integration of the former Soviet Republics - Vymyatnina, Yulia; Antonova, Daria; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Creating a Eurasian Union offers a detailed analysis of the economies of the former Customs Union of Russia, Belarus, and Kazakhstan and the proposed Eurasian Union.
Keywords: Economic theory; Econometrics; Public finance; Economic policy; Economic growth; Regional economics; Spatial economics